Preferensi Arisan Sebagai Sumber Modal Di Era Digital : Studi Di Pasar Darmo Trade Center - Moh. Afandi Yaasin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
The purpose of the research is to understand and know the preferences of traders in the Darmo Trade Center Market (DTC) in choosing Arisan as a source of capital in the digital era. In its implementation, the method used in this study is a descriptive qualitative method. The data collection in the study was obtained from interviews and observations. Based on the description of the results of the election that has been done by researchers, it can be concluded that there are six preferences of traders choosing arisen as a source of capital, namely: Easy to Reach, Avoid the Element of Riba, Without Guarantees, Easy and Not Burdensome Payment Procedures, Helping in Setting Aside Income, Feeling Calmer. .